A Rare Cause of Gross Hematuria in Childhood: Renal Lymphangiectasia - Çağla Serpil Doğan; Gülşah Kaya Aksoy (Galenos Yayinevi, 2018)
Renal lymphangiectasia is a rare disorder characterized by cystic malformation of the lymphatic ducts surrounding the kidney. In this article, an adolescent who presented with painless gross hematuria, hypertension, polycythemia and who was determined to have left perirenal lymphangiectasia and ipsilateral decreased renal function on imaging studies is reported.